Africa the Heart of Light: Barbara Kingsolver’s The Poisonwood Bible - Taher, Isra Hashim; Abdulkareem, Tahira Makki (Al-Adab Journal, 2019)
Barbara Kingsolver (1955-) is a Young Adult fiction writer who combines both her awareness of sociopolitical issues and her love of nature to produce works that both educate and entertain her young readers. Kingsolver’s work, The Poisonwood Bible (1998) addresses the issue of finding spirituality in midst of war, turmoil, and clash of cultures. Until the publication of The Poisonwood Bible the image of Africa in the western literature has been that of an uncivilized place torn by political conflicts, economic crises, ignorance and filled with spiritual darkness. Kingsolver shatters that image by asserting the cultural richness of Africa. She celebrates the diversity of cultures and religious beliefs there. The Poisonwood Bible tells the story of the Prices, a missionary family from Georgia, who are sent to the Congo in 1959 to "save Africa for Jesus". In Africa the spiritual values of the Prices are tested and found lacking when measured against the supposed savagery of the Africans. The paper discusses how Kingsolver challenges the stereotypical representation of Africans by distrusting the materialism brought by western civilization and hailing the Africans’ spiritual belief in nature which ultimately overpowers the Christian beliefs of the missionary family that prove to be unsuitable for the natives’ needs.